The incidence and repetition of hospital-treated deliberate self harm: findings from the world's first national registry. - Ivan J Perry; Paul Corcoran; Anthony P Fitzgerald; Helen S Keeley; Udo Reulbach; Ella Arensman (PLoS ONE, 2012)
Background Suicide is a significant public health issue with almost one million people dying by suicide each year worldwide. Deliberate self harm (DSH) is the single most important risk factor for suicide yet few countries have reliable data on DSH. We developed a national DSH registry in the Republic of Ireland to establish the incidence of hospital-treated DSH at national level and the spectrum and pattern of presentations with DSH and repetition. Methods and findings Between 2003 and 2009, the Irish National Registry of Deliberate Self Harm collected data on DSH presentations to all 40 hospital emergency departments in the country. Data were collected by trained data registration officers using standard methods of case ascertainment and definition. The Registry recorded 75,119 DSH presentations involving 48,206 individuals. The total incidence rate fell from 209 (95% CI: 205-213) per 100,000 in 2003 to 184 (95% CI: 180-189) per 100,000 in 2006 and increased again to 209 (95% CI: 204-213) per 100,000 in 2009. The most notable annual changes were successive 10% increases in the male rate in 2008 and 2009. There was significant variation by age with peak rates in women in the 15-19 year age group (620 (95% CI: 605-636) per 100,000), and in men in the 20-24 age group (427 (95% CI: 416-439) per 100,000). Repetition rates varied significantly by age, method of self harm and number of previous episodes. Conclusions Population-based data on hospital-treated DSH represent an important index of the burden of mental illness and suicide risk in the community. The increased DSH rate in Irish men in 2008 and 2009 coincided with the advent of the economic recession in Ireland. The findings underline the need for developing effective interventions to reduce DSH repetition rates as a key priority for health systems.